2015
DOI: 10.1161/strokeaha.115.010860
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil May Alleviate Poststroke Fatigue

Abstract: Modafinil is a wake promoting drug useful for treatment of excessive sleepiness in narcolepsy, shift work sleep disorder, and obstructive sleep apnea. Numerous other indications, including treatment of fatigue in multiple sclerosis, have been suggested but are still debated.14 The neurobiochemical effects of modafinil are complex and not fully understood. 15 The primary effects seem to involve inhibiting reuptake by dopamine and norepinephrine transporters. Furthermore, it is known to have some effects on sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
0
33
0
1
Order By: Relevance
“…Thus, SSRIs may not be effective for PSF. Modafinil, a drug originally used for patients with hypersomnia or narcolepsy, was used in a recent randomized, placebo-controlled trial [ 152 ]. Forty-one patients were treated with either 400 mg modafinil or placebo.…”
Section: Post-stroke Fatiguementioning
confidence: 99%
“…Thus, SSRIs may not be effective for PSF. Modafinil, a drug originally used for patients with hypersomnia or narcolepsy, was used in a recent randomized, placebo-controlled trial [ 152 ]. Forty-one patients were treated with either 400 mg modafinil or placebo.…”
Section: Post-stroke Fatiguementioning
confidence: 99%
“…A recent study of modafinil therapy in a more acute population of patients with stroke in hospital, which did not recruit to target, was not able to show a treatment effect of modafinil on the MFI. 14 Of note is that the placebo group in this study also had a decline in fatigue during their hospital stay, something often observed in the initial recovery phase after acute stroke. 23 Importantly, our study assessed patients more than 3 months post-stroke, rather than in the in-hospital setting.…”
Section: Discussionmentioning
confidence: 59%
“…Modafinil has been tested in clinical trials to alleviate fatigue in multiple sclerosis and inpatient stroke patients with mixed results in small or incomplete studies. 13,14 …”
mentioning
confidence: 99%
“…On the other hand, neurons from this nucleus seem to be be the site of action for a drug used to treat narcolepsy, modafinil [ 30 ]. Modafinil is also used to treat fatigue in MS patients [ 31 ] and it has been recently shown to be effective in alleviating post-stroke fatigue [ 32 ].…”
Section: Discussionmentioning
confidence: 99%